(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
Toxoplasmosis is one of the most important and common zoonotic diseases worldwide with an infection rate ranging between 20-80% of the world’s population. The affecting in a wide range of mammals, including humans, causes significant disease effects on human health and economic animals. The parasite has an amazing ability to spread within the host’s body and uses various strategies to overcome the blood-brain barrier, with the ability to exist for life within the cells of the infected host. The current study aimed at following up the histopathological changes in the brain of mice experimentally infected with toxoplasmosis. A placenta samples were collected from Al-Salam Teaching Hospital in Mosul, and the parasite was isolated and injection of 100 tissue cyst into the peritoneal cavity of laboratory mice. The animals were divided into three groups, and the mice were dissected after 21, 30 and 40 days of infection period in order to study histopathological changes in the cortex, hippocampus and amygdala. The results of the numbers of parasite cysts in the hippocampus, amygdala and cortex showed an increase in the number of parasite cysts in the cortex compared with the hippocampus and amygdala, the histological sections showed in addition to vacuolar degenerative changes and Apoptosis. After 30 days of infection, the results showed a decrease in body weight in males. The histological sections showed necrosis of the granular cell layer, edema around the nerve axons. The results of the third group, after 40 days of infection, showed a decrease in body weight in males and females compared with the control group and an increase in brain weight in males. The histological sections showed the loss of nuclei in the cells of the basal medial nuclei, vacuolar degeneration, in addition to the presence of vacuolization.